Recombinant T-Cell Receptor Ligand (RTL) for Treatment of Multiple Sclerosis: A Double-Blind, Placebo-Controlled, Phase 1, Dose-Escalation Study. (5th April 2012) - Yadav, Vijayshree; Bourdette, Dennis N.; Bowen, James D.; Lynch, Sharon G.; Mattson, David; Preiningerova, Jana; Bever, Christopher T.; Simon, Jack; Goldstein, Andrew; Burrows, Gregory G.; Offner, Halina; Ferro, Al J.; et al.
Abstract : Background . Recombinant T-cell receptor ligand 1000 (RTL1000) is a single-chain protein construct containing the outer two domains of HLA-DR2 linked to myelin-oligodendrocyte-glycoprotein- (MOG-) 35–55 peptide. Analogues of RTL1000 induce T-cell tolerance, reverse clinical and histological disease, and promote repair in experimental autoimmune encephalomyelitis (EAE) in DR2 transgenic, C57BL/6, and SJL/J mice. Objective . Determining the maximum tolerated dose, safety, and tolerability of RTL1000 in multiple sclerosis (MS) subjects. Methods . This was a multicenter, Phase I dose-escalation study in HLA-DR2 + MS subjects. Consecutive cohorts received RTL1000 doses of 2, 6, 20, 60, 200, and 100 mg, respectively. Subjects within each cohort randomly received a single intravenous infusion of RTL1000 or placebo at a 4 : 2 ratio. Safety monitoring included clinical, laboratory, and brain magnetic resonance imaging (MRI) evaluations. Results . Thirty-four subjects completed the protocol. All subjects tolerated the 2–60 mg doses of RTL1000. Doses ≥100 mg caused hypotension and diarrhea in 3 of 4 subjects, leading to discontinuation of further enrollment. Conclusions . The maximum tolerated dose of RTL1000 in MS subjects is 60 mg, comparable to effective RTL doses in EAE. RTL1000 is a novel approach for MS treatment that may induce immunoregulation without immunosuppression and promote neural repair.